Science Augmented Reality Program Media for Elementary School Students - AF Suryaning Ati MZ; Mala Rosa Aprillya; Mufti Ari Bianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Well-designed media within a certain time limit can stimulate the emergence of an internal dialogue in students. One of the interesting media that can be used to increase students' motivation and passion for learning is Augmented Reality (AR) media. The aims of this study was to develop the Science Augmented Reality Program (SARP) media in assisting the learning process for elementary school students. This study applied the four-D method. The research data included the results of the validity and effectiveness of using the Science Augmented Reality Program (SARP) media. The research subjects in this study were fourth grade elementary school students. Validity includes the validity of learning materials, the validity of design, and the validity of learning media from two experts. Meanwhile, the effectiveness test was perceived from the results of limited trials and field trials. The product was tested on sixth grade elementary school students on natural sciences material. The results showed that the percentage of learning material validity test results was 95% with a very valid category, the percentage of learning media design validity test results was 97% with a very valid category, the percentage of learning media validity test results was 92% with a very valid category. Overall, it is concluded that the Science Augmented Reality Program media is very suitable and effective to be applied as natural science learning media in elementary schools.